Making better environmental decisions: an alternative to risk assessment - O'Brien, Mary (Cambridge, 2000)
"For the past quarter-century, government and the private sector have relied heavily on risk assessment for making decisions, allowing widespread environmental deterioration. Alternatives assessment is a simple, commonsense alternative to risk assessment. It is based on the premise that it is not acceptable to damage human and nonhuman health or the environment if there are reasonable alternatives. The approach calls for taking precautionary measures even if some cause-and-effect relationships have not been fully established scientifically. The process must involve an examination of the full range of alternatives, including no action at all. Equally important, it must be democratic and include potentially affected parties. ..."